1990
DOI: 10.3354/meps059019
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the pelagic food web in relation to water column structure in the Skagerrak

Abstract: The distribution, composition and activity of phytoplankton, and accompanying changes in specific activities of bacterioplankton and copepods, were related to variahons in the vertical structure of the water column along a transect through the Skagerrak in May 1987. The Skagerrak is charactenzed by a doming of the pycnocline, with a deep mixed layer along the periphery and a very shallow pycnochne in central parts Average phytoplankton size increased with the depth of the upper mixed layer, and the central str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 26 publications
3
21
0
3
Order By: Relevance
“…2B) would support our conclusion of a relatively higher flux of organic matter to bacteria in stratified than in mixed waters. Therefore, our results are consistent with the earlier notions that traditional food chains dominate in turbulent or mixed waters, whereas microbial food chains dominate in strongly stratified waters (Azam et al 1983, Hagström et al 1988, Kiørboe et al 1990, Legendre & Le Fèvre 1995.If physical forces such as turbulent mixing and temperature can be considered as influential regulating factors in plankton ecology (White et al 1991, Kirchman et al 1995, Peters et al 1998, Petersen et al 1998, we would expect to find trends similar to the BP/PP versus SST relationship observed in the Yellow Sea in other regions. Temporally independent (i.e.…”
supporting
confidence: 92%
“…2B) would support our conclusion of a relatively higher flux of organic matter to bacteria in stratified than in mixed waters. Therefore, our results are consistent with the earlier notions that traditional food chains dominate in turbulent or mixed waters, whereas microbial food chains dominate in strongly stratified waters (Azam et al 1983, Hagström et al 1988, Kiørboe et al 1990, Legendre & Le Fèvre 1995.If physical forces such as turbulent mixing and temperature can be considered as influential regulating factors in plankton ecology (White et al 1991, Kirchman et al 1995, Peters et al 1998, Petersen et al 1998, we would expect to find trends similar to the BP/PP versus SST relationship observed in the Yellow Sea in other regions. Temporally independent (i.e.…”
supporting
confidence: 92%
“…Anon., 1993;Rosenberg et al, 1996;Miskov-Nodland et al, 1999) and some papers on crustacean mesozooplankton (e.g. Båmstedt, 1983;Kiørboe et al, 1990;Tiselius et al, 1991) and euphausids (e.g. Buchholz and Boysen-Ennen, 1988;Bøhle and Moksness, MS 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This often results in a summer "dome" or "ridge" of the pycnocline in the central area of the Skagerrak (Fonselius, 1996, Danielssen et al, 1997 that also influences the structure of the near-surface phyto-and zooplankton community (e.g. Kiørboe et al, 1990;Kahru and Leeben, 1991). The third feature, of particular significance for the deep-water community, is the sub-surface inflow of saline Atlantic Water along the southern slope of the deep-water basin (Rohde, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In various aquatic environments, protozoan grazing (Rassoulzadegan & Sheldon 1986, Sherr et al 1992) and viral lysis (Proctor & Fuhrman 1992, Suttle 1994 have been related to the variations in bacterial abundance. Meanwhile, other research concluded that the physical stability of the water column, which largely controls the trophic conditions, determines bacterial distribution and production and their quantitative role in microbial food-web processes (Cushing 1989, Kiørboe et al 1990, Cho et al 2001, Shiah et al 2001. In combination, these results suggest that the factors controlling bacterial populations are system-dependent.…”
Section: Introductionmentioning
confidence: 60%